Anaerobic threshold assesment through the ventilatory method during roller-ski skating testing: Right or wrong - Fabre, N.; Bortolan, L.; Pellegrini, B.; Zerbini, L.; Mourot, L.; Schena, F. (The Journal of Strength and Conditioning Research, 2012)
This study aimed at questioning the validity of the ventilatory method to determine the anaerobic threshold (respiratory compensation point [RCP]) during an incremental roller-ski skating test to exhaustion. Nine elite crosscountry skiers were evaluated. The skiers carried out an incremental roller-ski test on a treadmill with the V2 skating technique. Ventilatory parameters were continuously collected breath by breath, thanks to a portable gas exchange measurement system. Poling signal was obtained using instrumented ski poles. For each stage, ventilatory and poling signals were synchronized and averaged. The poor coefficient of interobserver reliability for the time at RCP confirmed the great difficulty felt by the 3 blinded reviewers for the RCP determination. Moreover, the reviewer agreed with the impossibility of determining RCP in 4 of the 9 skiers. There was no significant difference between breathing frequency (Bf) and poling frequency (Pf) during the last 8 stages. However, it seems that the differences observed during the first stages arose from the use of either a strictly 1:1 or a 1:2 Bf to Pf ratio when the exercise intensity was still moderate. So, even if there were significant differences between the frequencies, the Bf was strictly subordinate to the Pf during the entire test. In the same way, the normalized tidal volume and peak poling forces curves were superposable. These findings showed that when the upper body is mainly involved in the propulsion, the determinants of the ventilation are strictly dependent on the poling pattern during an incremental test to exhaustion. Thus, during roller-ski skating, the determination of RCP must be used cautiously because too much depending on mechanical factors.